2002
DOI: 10.1109/tgrs.2002.800232
|View full text |Cite
|
Sign up to set email alerts
|

Semi-empirical model of the ensemble-averaged differential Mueller matrix for microwave backscattering from bare soil surfaces

Abstract: Abstract-A semi-empirical model of the ensemble-averaged differential Mueller matrix for microwave backscattering from bare soil surfaces is presented. Based on existing scattering models and data sets measured by polarimetric scatterometers and the JPL AirSAR, the parameters of the co-polarized phase-difference probability density function, namely the degree of correlation and the co-polarized phase-difference , in addition to the backscattering coefficients 0 , 0 and 0 , are modeled empirically in terms of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
141
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(146 citation statements)
references
References 19 publications
(42 reference statements)
2
141
0
3
Order By: Relevance
“…Radar experiments have shown that the CPD is close to 0 for soil at small incidence angles but the CPD shows an increasing standard deviation for rough surfaces. It has also been found that the CPD increases to a few tens of degrees with increasing incidence angle for rough soil (Sarabandi, 1992;Oh et al, 2002). The CPD is also influenced by vegetation cover, especially for oriented vegetation .…”
Section: Contribution Of a Rough Ground Surfacementioning
confidence: 88%
See 2 more Smart Citations
“…Radar experiments have shown that the CPD is close to 0 for soil at small incidence angles but the CPD shows an increasing standard deviation for rough surfaces. It has also been found that the CPD increases to a few tens of degrees with increasing incidence angle for rough soil (Sarabandi, 1992;Oh et al, 2002). The CPD is also influenced by vegetation cover, especially for oriented vegetation .…”
Section: Contribution Of a Rough Ground Surfacementioning
confidence: 88%
“…Remote sensing methods provide therefore a complementary tool to the detailed ground measurements such as CT or in situ measurements. For example, radio-wave birefringence measurements have been used to explore internal structures of ice sheets and glaciers with polarized radio-and microwaves (e.g., Hargreaves, 1977Hargreaves, , 1978Fujita et al, 2006;Matsuoka et al, 2009;Parrella et al, 2016). With passive microwave sensors, strong polarimetric signatures have also been found over the Greenland ice sheet: in Li et al (2008), the observed signatures could not be explained by surface features and were discussed with respect to microstructural variations of snow anisotropy, as predicted by Tsang (1991).…”
Section: Radio and Microwave Remote Sensing Observations Of The Dielementioning
confidence: 99%
See 1 more Smart Citation
“…However, many of these methods perform poorly when used to predict soil moisture for natural surfaces (i.e., that depart from bare soil) using radar backscatter data due to their restrictive assumptions [17]. To circumvent these problems, semi-empirical models were developed to predict soil moisture and surface roughness from radar imagery [17,18]. These models use co-polarized back-scatter coefficients, in the horizontal transmit-receive (HH) and/or vertical transmit-receive polarization (VV) to predict soil moisture as they are less sensitive to system noise and cross-interference than the weaker cross-polarized coefficients (i.e., HV and VH).…”
Section: Broad Range Of Model Assumptions and Predictive Accuracymentioning
confidence: 99%
“…Most field studies and models assume bare soil conditions to measure soil moisture with radar remote sensing and modeling backscatter contributions of the soil surface and subsurface [Dubois et al, 1995, Fung et al, 1992, Merzouki et al, 2011, Oh, 2004, Oh et al, 1992, Oh et al, 2002, Rahman et al, 2008, Verhoest et al, 2007, Zribi and Dechambre, 2003]. …”
Section: Remote Sensing Of Soil Moisturementioning
confidence: 99%